2018
DOI: 10.7717/peerj.4311
|View full text |Cite
|
Sign up to set email alerts
|

Molecular systematics of the subfamily Limenitidinae (Lepidoptera: Nymphalidae)

Abstract: We studied the systematics of the subfamily Limenitidinae (Lepidoptera: Nymphalidae) using molecular methods to reconstruct a robust phylogenetic hypothesis. The molecular data matrix comprised 205 Limenitidinae species, four outgroups, and 11,327 aligned nucleotide sites using up to 18 genes per species of which seven genes (CycY, Exp1, Nex9, PolII, ProSup, PSb and UDPG6DH) have not previously been used in phylogenetic studies. We recovered the monophyly of the subfamily Limenitidinae and seven higher clades … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 33 publications
5
33
2
Order By: Relevance
“…The reasons behind the close genetic relationships of several groups of species is not entirely clear, but may have to do with the repeated contraction and expansion of the forests in Africa, especially during the Miocene and Pleistocene. Similar patterns appear to be the case in other forest specialist genera of the family Nymphalidae: Charaxes Ochsenheimer, 1816 (Aduse-Poku et al 2009), Cymothoe Hübner, 1819(van Velzen et al 2013 and Euphaedra Hübner, 1819 (Dhungel and Wahlberg 2018). Mylothris and the nymphalid genera cited appear to be going through rapid speciation in African forests and they require further study to understand the driving mechanisms…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The reasons behind the close genetic relationships of several groups of species is not entirely clear, but may have to do with the repeated contraction and expansion of the forests in Africa, especially during the Miocene and Pleistocene. Similar patterns appear to be the case in other forest specialist genera of the family Nymphalidae: Charaxes Ochsenheimer, 1816 (Aduse-Poku et al 2009), Cymothoe Hübner, 1819(van Velzen et al 2013 and Euphaedra Hübner, 1819 (Dhungel and Wahlberg 2018). Mylothris and the nymphalid genera cited appear to be going through rapid speciation in African forests and they require further study to understand the driving mechanisms…”
Section: Discussionsupporting
confidence: 53%
“…The fragmentation of the forests in the Miocene and Pleistocene may have contributed to the diversification of the group, perhaps by causing populations to be fragmented and isolated from each other. This appears to be a common pattern in forest dwelling butterflies of Africa (Aduse-Poku et al 2009;van Velzen et al 2013;Dhungel and Wahlberg 2018), but the mechanisms leading to their diversification are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the samples used in this study were from dry, pinned specimens collected fewer than 10 years ago, and the oldest was collected from 17 years ago. In addition, we added Sanger sequence data from 32 Neptis and 6 outgroup samples included in the study by Dhungel & Wahlberg (2018) to compare phylogenetic results based on the three commonly used loci employed by this recent Sanger study (cytochrome c oxidase subunit I, COI; elongation factor-1a, EF-1a; glycer-aldehyde-3-phosphate dehydrogenase, GAPDH) with the results were obtained using nearly 30 times more loci (Zhang et al, 2019). Our sample represents >80% of recognized Palearctic Neptis species, two-thirds of recognized Oriental and Australasian Neptis species, and ∼20% of recognized African Neptis species (Lamas, 2015).…”
Section: Taxon Samplingmentioning
confidence: 99%
“…Recent molecular phylogenetic studies demonstrated that the genus Neptis is not monophyletic (Zhang et al, 2011;Chen et al, 2017;Dhungel & Wahlberg, 2018), nor are the traditional species groups within it as originally described by Eliot (1969). Phylogenetic studies including Neptis have failed to arrive at a convincing evolutionary picture of the genus because they sampled too few Neptis species and/or used a small number of loci, resulting in weakly supported relationships (Chen et al, 2007;Wu et al, 2007aWu et al, , 2007bZhang et al, 2008aZhang et al, , 2008bWahlberg et al, 2009;Mullen et al, 2010;Zhang et al, 2011;Wu et al, 2016;Dhungel & Wahlberg, 2018). In the present study, we used 89 loci to reconstruct phylogenetic relationships among Neptis butterflies and to test the usefulness of Zhang et al's (2019) PCR-generated probes for inferring relationships among species.…”
Section: Introductionmentioning
confidence: 96%
“…It should be noted here that a recent molecular phylogeny focusing on the nymphalid subfamily Limenitidinae, based on both COI and several nuclear markers, indicated that the genus Euphaedra branches out into two clades, including one in which species are not all very well resolved (i.e., low bootstrap values; Dhungel and Wahlberg 2018). Although E. eberti was not included in that phylogeny, it apparently belongs to that same clade as one of the species we employed in the phylogeny reported here, E. spatiosa, belongs to that clade in the Dhungel and Wahlberg (2018) phylogeny and is shown here to be very closely related to E. eberti (Fig. 7).…”
Section: Discussionmentioning
confidence: 88%